Application of Parallel Multiparametric Cell-Based FLIPR Detection Assays for the Identification of Modulators of the Muscarinic Acetylcholine Receptor 4 (M4). (August 2015) - Smith, Emery; Chase, Peter; Niswender, Colleen M.; Utley, Thomas J.; Sheffler, Douglas J.; Noetzel, Meredith J.; Lamsal, Atin; Wood, Michael R.; Conn, P. Jeffrey; Lindsley, Craig W.; Madoux, Franck; Acosta, Mary; et al.
Muscarinic acetylcholine receptors (mAChRs) have long been viewed as viable targets for novel therapeutic agents for the treatment of Alzheimer's disease and other disorders involving impaired cognitive function. In an attempt to identify orthosteric and allosteric modulators of the muscarinic acetylcholine receptor M4 (M4 ), we developed a homogenous, multiparametric, 1536-well assay to measure M4 receptor agonism, positive allosteric modulation (PAM), and antagonism in a single well. This assay yielded a Z′ of 0.85 ± 0.05 in the agonist, 0.72 ± 0.07 in PAM, and 0.80 ± 0.06 in the antagonist mode. Parallel screening of the M1 and M5 subtypes using the same multiparametric assay format revealed chemotypes that demonstrate selectivity and/or promiscuity between assays and modalities. This identified 503 M4 selective primary agonists, 1450 PAMs, and 2389 antagonist hits. Concentration-response analysis identified 25 selective agonists, 4 PAMs, and 41 antagonists. This demonstrates the advantages of this approach to rapidly identify selective receptor modulators while efficiently removing assay artifacts and undesirable compounds.